2008
DOI: 10.1093/jxb/ern168
|View full text |Cite
|
Sign up to set email alerts
|

Microarray expression profiling of Arabidopsis thaliana L. in response to allelochemicals identified in buckwheat

Abstract: Buckwheat (Fagopyrum esculentum Moench) is an important annual plant cultivated for grain or as a cover crop in many countries, and it is also used for weed suppression in agro-economic systems through its release of allelochemicals. Little is known, however, concerning the mode of action of allelochemicals or plant defence response against them. Here, microarrays revealed 94, 85, and 28 genes with significantly higher expression after 6 h of exposure to the allelochemicals fagomine, gallic acid, and rutin, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 45 publications
(62 reference statements)
0
45
1
1
Order By: Relevance
“…Thus, different auxin signaling genes might have diverse functions in the regulation of secondary xylem differentiation. The diverse functions might be important for maintaining auxin balance and responding to auxin stimulus (Golisz et al, 2008;Péret et al, 2012). Genes that were more transcribed in the lignified xylem might have a function in calcium ion transport and response to auxin stimulus (Hagen and Guilfoyle, 2002), whereas auxin-related genes that were preferentially expressed in the newly formed xylem were likely to have a role in cell wall modification in response to auxin (Tamaoki et al, 2008).…”
Section: Differential Expression Of Hormone-related Genesmentioning
confidence: 99%
“…Thus, different auxin signaling genes might have diverse functions in the regulation of secondary xylem differentiation. The diverse functions might be important for maintaining auxin balance and responding to auxin stimulus (Golisz et al, 2008;Péret et al, 2012). Genes that were more transcribed in the lignified xylem might have a function in calcium ion transport and response to auxin stimulus (Hagen and Guilfoyle, 2002), whereas auxin-related genes that were preferentially expressed in the newly formed xylem were likely to have a role in cell wall modification in response to auxin (Tamaoki et al, 2008).…”
Section: Differential Expression Of Hormone-related Genesmentioning
confidence: 99%
“…A number of recent studies have reported cellular and molecular processes involved in the production of allelochemicals and the response of target plants (Baerson et al, 2005;Dayan, 2006;Ding et al, 2007;Golisz et al, 2008;Song et al, 2008). During the molecular oxygen reduction process, intermediate molecules known as Reactive Oxygen Species (ROS) [e.g., superoxide (O .− 2 ), hydrogen peroxide (H 2 O 2 ) and hydroxyl radical (OH . )]…”
Section: Releasing Allelopathic Compounds Into the Environmentmentioning
confidence: 99%
“…More recently, an analysis of the gene expression of A. thaliana though a micro-array following exposure to fagomine, gallic acid and rutin has revealed that genes expressed in response to allelochemicals share the same pathways triggered during the response to abiotic and biotic stress (Golisz et al, 2008).…”
Section: Genetic Improvement Of Allelopathic Activity In Cropsmentioning
confidence: 99%
“…Nestes casos, a agricultura se utiliza da alelopatia do sorgo diminuindo assim o uso de controles herbicidas sintéticos danosos ao meio ambiente favorecendo dessa maneira uma produção de grãos mais saudável ao consumo. ALELOPATIA A alelopatia é a capacidade de um organismo produzir metabólitos que atuam inibindo ou estimulando crescimento ou o desenvolvimento de outros organismos, que estão próximos e que competem por recursos limitados como: nutrientes, água e luz golisz et al, 2008).…”
Section: Produção De Sorgo No Brasilunclassified